Aldosterone Blockade Reduces Mortality without Changing Cardiac Remodeling in Spontaneously Hypertensive Rats - Cezar, Marcelo D. M. [UNESP]; Damatto, Ricardo L. [UNESP]; Martinez, Paula F.; Lima, Aline R. R. [UNESP]; Campos, Dijon H. S. [UNESP]; Rosa, Camila M. [UNESP]; Guizoni, Daniele M. [UNESP]; Bonomo, Camila [UNESP]; Cicogna, Antonio Carlos [UNESP]; Gimenes, Rodrigo [UNESP]; Pagan, Luana U. [UNESP]; Okoshi, Marina Politi [UNESP]; et al. (Karger, 2013)
Background: The role of aldosterone blockers during transition from long-term compensated hypertrophy to dilated failure is not completely understood. In this study we evaluated the effects of early administration of spironolactone on cardiac remodeling, myocardial function, and mortality in spontaneously hypertensive rats (SHR). Methods: Sixteen-month-old SHR received no treatment (SHR-C, n=72) or spironolactone (SHR-SPR, 20 mg/kg/day, n=34) for six months. Echocardiogram was performed before and after treatment. Myocardial function was analyzed in left ventricular (LV) papillary muscle preparations. Myocardial collagen aund hydroxyproline concentration were evaluated by morphometry and spectrophotometry, respectively. LV gene expression was assessed by real time RT-PCR. Statistics: Student's t test; Log rank test (Kaplan Meyer). Results: SHR-C and SHR-SPR presented mortality rates of 71 and 38%, respectively (p=0.004). Systolic arterial pressure did not differ between groups (SHR-C 199 +/- 43; SHR-SPR 200 +/- 35 mmHg). Initial and final echocardiograms did not show significant differences in cardiac structures or LV function between groups. Myocardial function was similar between groups at basal and after inotropic stimulation. Collagen fractional area, hydroxyproline concentration, gene expression for alpha- and beta-myosin heavy chain, atrial natriuretic peptide, and Serca2a were not different between groups. Conclusion: Early spironolactone administration reduces mortality without changing cardiac remodeling in spontaneous hypertensive rats. Copyright (C) 2013 S. Karger AG, Basel
Keywords: Heart failure; Myocardial function; Echocardiogram; Spironolactone; Ventricular function; Papillary muscle